Draft Genome Sequence of the Marine Sediment-Derived Actinomycete Streptomyces xinghaiensis NRRL B24674(T) - Zhao, Xinqing (American Society for Microbiology, 2011)
Actinobacteria are a rich source of novel natural products. We recently characterized Streptomyces xinghaiensis NRRL B24674(T) as a novel species of marine origin. Here we report the draft genome sequence of this species. This is the first validly published marine streptomycete for which a genome sequence has been presented.